Landscape-level assessment of the distribution of the Sumatran rhinoceros in Bukit Barisan Selatan National Park, Sumatra - Wulan Pusparini; Hariyo Wibisono (Pachyderm)
We conducted the first systematic survey on Sumatran rhinoceros following a robust patch occupancy framework in 3,500 km 2 of Bukit Barisan Selatan National Park (BBSNP), Sumatra, Indonesia. We surveyed 55 grids (72.25 km 2 ) between November 2007 and July 2008 to generate a reliable estimate of the proportion of area occupied (occupancy) by the Sumatran rhinoceros. Rhinoceros signs, e.g. footprints, dung, tree twists and wallows, were recorded along 833 km of transect routes, and 1-km sampling interval was used to develop detection/non-detection history for each grid. Rhinoceros signs were detected on 11 grids producing a naïve occupancy of 0.2. Occupancy modelling was used to control for imperfect detection probability (P). Based on the Royle/Nichols Heterogeneity model we concluded that Sumatran rhinoceros occupied approximately 32% of the BBSNP area (SE = 0.09). Occupancy can serve as a robust surrogate for an index of abundance in a population-monitoring framework. Further analysis using the multi-season models of the technique on time series data and season/survey-specific covariates can provide management authorities with accurate information about changes in rhinoceros populations and assist in prioritizing conservation actions for the Sumatran rhinoceros in the region.